The physiology of world-class cross-country skiers - a reappraisal of the success factors for performance - Sandbakk, O. (3rd International Congress on Science and Nordic Skiing - ICSNS 2015. 5-8 June 2015, Vuokatti, Finland, 2015)
Due to more effective training and tremendous improvements in equipment and track preparation, the speed of cross-country ski races has increased more than that of any other Olympic endurance sport over the last 30 years. In addition to the introduction of the skating technique, also pursuit, mass-start and sprint races have been introduced during this period. Accordingly, a reappraisal of the success factors for performance in today's cross-country skiing events has been required.